Effect of light on seed germination of 14 cactus species from Peru - Jara-Peña, Enoc; Quiroz, Aarón J.; Vela Arce, Miguer (Instituto de Ecología, A.C., 2024)
Background and Aims: The main threats to the conservation of cacti in Peru are the expansion of agricultural areas, mining, road construction, urban expansion, and population growth, causing fragmentation and habitat destruction. The disturbed ecosystems could be restored with seeds and seedlings of cacti. This research aimed to evaluate the effect of light on the germination of Peruvian cacti seeds. Methods: Cactaceae seeds were collected in the departments of Ancash, Apurimac, Arequipa and Huánuco. The experiment was conducted under controlled conditions using a completely randomized experimental design. Seed germination of the species Austrocylindropuntia floccosa, Armatocereus mataranus subsp. ancashensis, Browningia candelaris, Corryocactus aureus, C. brevistylus subsp. brevistylus, Cumulopuntia ignescens, Espostoa lanata subsp. ruficeps, Haageocereus platinospinus, Lobivia maximiliana subsp. westii, Opuntia macbridei, Trichocereus cuzcoensis, T. santaensis, Tunilla soehrensii and Weberbauerocereus weberbaueri was evaluated with both light and dark treatments, each with five replicates. Incubation took place in a growth chamber under a 12-hour light/12 hours dark photoperiod and temperature regimes ranging from 18 to 25°C. The average seed mass, germination time, and germination index relative to light were also calculated. Key results: Of the 14 species evaluated, 12 species germinated with light treatment, and two species germinated in both light and dark. Conclusions: The highest seed mass was observed in Austrocylindropuntia floccosa, while the lowest mass was recorded in Espostoa lanata subsp. ruficeps. Armatocereus mataranus subsp. ancashensis exhibited a germination period of 20.80 days, in contrast to Weberbauerocereus weberbaueri, which germinated within 10 days. Twelve species exhibited positive photoblastic responses, while Armatocereus mataranus subsp. ancashensis and Austrocylindropuntia floccosa demonstrated photoblastic neutrality.